Factors Influencing Tourist Behavioral Intentions at Southeast Asian Specialty Restaurants in Xinglong, Hainan, China - Zheng, Liqiao; Siriwattana, Srochinee (International Journal of Development Administration Research, 2025)
This study examines how different customer groups perceive the authenticity of Southeast Asian restaurants in Xinglong, Hainan, and how these perceptions affect satisfaction and recommendation intention. Using a sequential mixed-methods design, the research first conducted in-depth interviews with 30 participants including restaurant owners, chefs, overseas Chinese, and local residents to explore authenticity across food, environment, and service. Insights from this phase guided a structured questionnaire distributed to restaurant patrons. A total of 466 valid responses were collected from four groups: tourists (127), returned overseas Chinese (43), local residents (112), and students (184). Structural Equation Modeling (SEM) was used to assess relationships between authenticity perceptions, perceived value, satisfaction, and behavioral intention. Results show that food authenticity has the strongest positive influence on perceived value, satisfaction, and recommendation intention, followed by service and environmental authenticity. Group differences emerged: tourists and students respond more to environmental ambiance and service hospitality, while local residents and overseas Chinese emphasize traditional food flavor and preparation. This research contributes to cross-regional food cultural production by underscoring the role of authentic service and culinary integrity in shaping consumer experience. Practically, it supports Xinglong’s shift from sightseeing to culturally immersive tourism, suggesting that strengthening food and service authenticity can deepen visitor engagement and cultural identity. The findings offer guidance for local government, restaurant operators, and tourism developers aiming to preserve culinary heritage while meeting diverse customer expectations